2018
DOI: 10.1093/geronb/gby129
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Inequality at the End of Life?: Racial Disparities in Impairment in the Time Before Death

Abstract: Objectives Drawing from cumulative inequality (CI) theory, the current study examined racial disparities in impairment as individuals approached death to determine whether proposed mechanisms hypothesized to fuel or diminish racial disparities at late ages were at work at the end of individualized life spans. Method Black–white disparities were analyzed among decedents using latent growth curves based on the data from the Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Taylor and colleagues specifically studied trajectories of ADL limitations in the years prior to death and found that while racial disparities in functional status generally diminish in late old age, the trajectories diverge in the last two years before death with the curve becoming steeper for non-Hispanic African Americans. 6 This is also consistent with the study by Kail and colleagues who found that while the risk of functional limitation was similar among White non-Hispanic, African American non-Hispanic, and Hispanic older adults when they had no comorbidities, the curves for both African Americans non-Hispanics and Hispanics became steeper when comorbidities were present. 25 One possible reason for racial disparities in functional status is neighborhood segregation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Taylor and colleagues specifically studied trajectories of ADL limitations in the years prior to death and found that while racial disparities in functional status generally diminish in late old age, the trajectories diverge in the last two years before death with the curve becoming steeper for non-Hispanic African Americans. 6 This is also consistent with the study by Kail and colleagues who found that while the risk of functional limitation was similar among White non-Hispanic, African American non-Hispanic, and Hispanic older adults when they had no comorbidities, the curves for both African Americans non-Hispanics and Hispanics became steeper when comorbidities were present. 25 One possible reason for racial disparities in functional status is neighborhood segregation.…”
Section: Discussionsupporting
confidence: 90%
“…Although health-related discrepancies between Black non-Hispanic and White non-Hispanic Americans are wide during middle age, they tend to narrow in old age. 6 Functional trajectories for Black non-Hispanic and White non-Hispanic older adults are very similar until around the last year before death when they diverge, with Black non-Hispanic older adults experiencing a sharper trajectory of functional decline.…”
mentioning
confidence: 99%
“…CAD theory provides a framework for understanding how advantages and disadvantages accumulate over the life course. This perspective—first developed in sociology ( 9–11 ) and increasingly used to inform gerontological research ( 6 , 12 , 13 )—situates individual trajectories in the context of structural factors which may exacerbate or ameliorate previous (dis)advantages, with consequences for individual health and well-being in later life and population-level inequality.…”
Section: Cumulative (Dis)advantage and Disappearing Disparities In La...mentioning
confidence: 99%